Mengapa Pemerintah Daerah Mengadopsi Rencana Kota: Penyidikan Pada 40 Pemerintah Daerah Tingkat II - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Urban (spatial) plans are a relatively new urban management tool that was adopted at varying rates by local governments in Indonesia. Central government efforts to induce them to adopt urban plans are only fairly successful. This study tries to discover underlying local factors that might affect the rates of adoption of urban plans by local governnients. Utilizing the large body of innovation literature, this study investigates the effects of local political culture, economic robustness, and population size, as well as internal organizational characteristics of the Thcal government on its propensity to adopt urban plans as a local policy innovation. It is found that such local environmental factors have strong effects on the adoption of urban plans by local government, raising further questions on how far capacity building efforts so far expended by the government would overcome the negative effects of organizational size discovered in this study.